Proliferation of Wharton jelly mesenchymal stem cells, derived by preserving the cells with reduced attachment rate, under various gas conditions - Shuvalova, N.S.; Kordium, V.A. (Вiopolymers and Cell, 2015)
Aim. To estimate the proliferation rates in cultures of the human Wharton jelly mesenchymal stem cells (WJ-MSCs), obtained by the method of preservation of spontaneously detached cells, in various gas mixtures, containing physiological oxygen concentrations. Methods. Starting from the first passage, WJ-MSC were cultured for 4 subsequent passages, 7 days between replating (“main” line”). At 0, 1 and 2 passage, day 3 of cultivation, conditioned media was collected and transferred to another flack with complete growth media. The attached cells from conditioned media were cultivated until the clones size and confluence (70–80 %) became sufficient for replating, and after that were subsequently passed with trypsin-EDTA solution (“side” lines). Besides the cultivation in standard condition of CO2-incubator, the cultivation was conducted in the nitrogen-based gas mixture (3 % oxygen, 4 % carbon dioxide, 93 % nitrogen) and argon-based gas mixture (3 % oxygen, 4 % carbon dioxide, 93 % argon). At each passage, the number of cells was counted. Results. The proliferation level in “side” lines, obtained from 0 and 1 passages, had a lot of similarities with that of “main” line. We observed the trend of multiplication rate reduction in “side” lines during in vitro maintenance, similar to that in “main” line. For cultures, obtained at the passage 2, the level of proliferation was significantly lower. The cultivation in both gas mixtures with 3 % O2 concentration had beneficial effect on the level of cell multiplication: the number of cells was significantly higher. The effect of argon-based mixture was more pronounced. Conclusion. The physiologic oxygen tension allows optimizing the cultivation of WJ-MSC, obtained by the suggested method of preserving the cells with reduced attachment ability.